A critical review of existing models for the origin of the South China Sea and a new proposed model - Jiang, Xin; Wang, Zhenchao (Journal of Asian Earth Sciences: X, 2021)
•Classic tectonic evolutionary models of South China Sea are compiled.•The origin of South China Sea is critically discussed.•A new integrated tectonic model is proposed. Being the largest marginal sea in the western Pacific Ocean, South China Sea (SCS) has been brought into focus since 1970s due to the prolific biological resources and fossil energy preserved in the deep-sea area, particularly tectonic-controlled structures that determine basin sedimentation and hydrocarbon accumulation. Understanding the origin and tectonic evolution of SCS is necessary to better constrain the location of various resources. In this paper, we synthesize mainstream perspectives on the SCS sea floor spreading, including pulling apart of SCS driven by plate strike-slip during Eocene-Miocene, opening up of the Proto-SCS in late Oligocene-Miocene by subduction beneath NW Borneo along the margin and further spreading during Late Oligocene-mid Miocene due to lithospheric mantle flow upwelling. Existing tectonic evolution models of SCS are reviewed and their controversies are discussed. An intergraded model is proposed to provide a comprehensive consideration on the interpretation of the SCS formation and development.